Proximal Femoral Replacement and Allograft Prosthesis Composite in the Treatment of Periprosthetic Fractures with Significant Proximal Bone Loss - Rasouli, Mohammad R (Orthop Surg, 2012)
Femoral bone loss due to periprosthetic fracture, a challenging problem in total hip arthroplasty (THA), is increasingly encountered due to a rise in the number of revision THAs performed. Allograft prosthesis composite (APC) and proximal femoral replacement (PFR) are two available options for management of patients with difficult type‐B(3) Vancouver periprosthetic fractures. The treatment algorithm for patients with these fractures has been extensively studied and is influenced by the age and activity level of the patient. APC is often preferred in young and active patients in an attempt to preserve bone stock while older and less active patients are considered candidates for PFR. In spite of the high rate of overall complications with these two procedures, reported survivorship is acceptable. Treating patients with these complicated fractures is fraught with complications and, even with successful treatment, the outcomes are not as promising as those associated with primary hip replacement. In this paper, we aimed to review available published reports about PFR and APC for treatment of periprosthetic fractures around THAs.